Difficulties on Reading and Writing Faced by Fifth Graders: a Case Study - Antika Yuniar Sedyowati; Muhammad Abduh (Universitas Pendidikan Ganesha, 2022)
Reading comprehension is crucial in everyday life and for success in school and work. One of the expectations of educators when students enter early stage of elementary school is that they can read and write. This research is a qualitative case study. This study aims to analyses the factors that contribute to students' literacy difficulties and provide solutions that can help fifth-grade students and schools. This research employs case study methodology using a qualitative approach. The participants of this study were fifth graders with I students who had reading and writing difficulties. Methods of data collection in this study use observation and interviews. Instrument used in this study are use observation sheets and interview guidelines. Using data triangulation, researchers used descriptive analysis to conclude the data results and validity. This result found that students still had difficulties in the process of reading and writing influenced by several factors: lack of student motivation so that the problems experienced do not improve, difficulty distinguishing letters and are often reversed, reading is still halting, constantly guessing readings, and problems recognizing meaningful words. In addition, the lack of parental attention to school education affects student development and learning. Teachers apply strategies or treatments to overcome these problems.